Skills for business studies. Advanced - Naunton, Jon (Oxford : Oxford University Press, 2012)
Skills for Business Studies teaches academic reading, writing and vocabulary skills for students of Business Studies and related degree programmes. The Skills for Business Studies companion can optionally be added to the Business Result package, and provides academic skills practice for Business Studies students. It is also available as a standalone title.
Keywords: English language -- Business -- Study and teaching -- Foreign speakers; English language -- Problems, exercises, etc